2010
DOI: 10.1111/j.1529-8817.2010.00836.x
|View full text |Cite
|
Sign up to set email alerts
|

THE CONTRIBUTION OF SUB‐SAHARAN AFRICAN STRAINS TO THE PHYLOGENY OF CYANOBACTERIA: FOCUSING ON THE NOSTOCACEAE (NOSTOCALES, CYANOBACTERIA)1

Abstract: To date, phylogenies have been based on known gene sequences accessible at GenBank, and the absence of many cyanobacterial lineages from collections and sequence databases has hampered their classification. Investigating new biotopes to isolate more genera and species is one way to enrich strain collections and subsequently enhance gene sequence databases. A polyphasic approach is another way of improving our understanding of the details of cyanobacterial classification. In this work, we have studied phylogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 73 publications
3
32
0
1
Order By: Relevance
“…Therefore, it cannot be excluded that C. curvispora is actually another morphotype of C. raciborskii. This is supported by a study from Thomazeau et al (2010), who concluded that C. curvispora cannot be distinguished genetically from C. raciborskii using 16S rRNA gene sequences. Cylindrospermopsis spp.…”
Section: Aphanizomenon Aphanizomenoides Ef534274supporting
confidence: 64%
See 1 more Smart Citation
“…Therefore, it cannot be excluded that C. curvispora is actually another morphotype of C. raciborskii. This is supported by a study from Thomazeau et al (2010), who concluded that C. curvispora cannot be distinguished genetically from C. raciborskii using 16S rRNA gene sequences. Cylindrospermopsis spp.…”
Section: Aphanizomenon Aphanizomenoides Ef534274supporting
confidence: 64%
“…Sphaerospermopsis aphanizomenoides GU197720 Sphaerospermopsis aphanizomenoides GU197719 Thomazeau et al 2010). McGregor and Fabbro (2000) have described coiled morphotypes of Australian C. raciborskii with a similar morphology to C. curvispora strain AB2011/30.…”
Section: Aphanizomenon Aphanizomenoides Ef534274mentioning
confidence: 99%
“…tenuis that match CYL rpoC1 primers and probes. In fact, a phylogenetic study of four genes (the 16S rRNA gene and hetR, nifH, and rpoC1 genes) of Anabaena morphospecies led to the conclusion that A. sphaerica is phylogenetically closer to Cylindrospermopsis and Raphidiopsis and, thus, should be considered a sister group with Cylindrospermopsis instead of Anabaena (35), thus supporting our assay design.…”
Section: Discussionmentioning
confidence: 70%
“…The sxtA data set was incremented with four sxtA sequences from GenBank (Supplementary data S1). For both alignments, Lyngbya wollei sequence was chosen as outgroup (Thomazeau et al, 2010).…”
Section: Alignment and Data Setmentioning
confidence: 99%